Parochial Altruism: Pitfalls and Prospects - Hannes Rusch (Frontiers Research Topics, 2016)
A number of recent influential publications have promoted the idea that the high levels of altruism and violent intergroup conflicts observed in humans might be the result of a joint evolution of behavioral traits causing cooperativeness among group members ('in-group love') and spite and aggression between members of different groups ('out-group hate'). This hypothesis, dating back to Darwin himself, has been dubbed 'parochial altruism'. While much empirical evidence has been collected which shows that humans readily condition their social behaviors on their conspecifics' group membership, a number of important questions still remain unanswered. These include: Which selective mechanisms are at work in the suggested co-evolution of in-group love and out-group hate: individual selection, kin selection, sexual selection? When and why does altruism become parochial? When and why can parochialism be altruistic? How does parochial altruism fare in comparison to other explanatory approaches to the question of why humans are altruistic and why they are collectively aggressive? Did human prehistory really offer the conditions required for parochial altruism to evolve? Is parochial altruism universal across situational contexts and cultures? Which factors can explain individual differences in parochial altruism? This Research Topic brings together current interdisciplinary works on the topic. Lab and field experiments using different methods critically investigate the antecedents, forms, and consequences of parochial altruism. As such, the Research Topic contributes to close some important research gaps but also provides an overview of the diverse methods for studying parochial altruism across scientific disciplines.